Corruption, Ritualism and Prophetic Role of the Catholic Church - Antonius Galih Arga Aryanto; Martinus Joko Lelono (Asosiasi Ahli Filsafat Keilahian Indonesia, 2021)
This interdisciplinary study attempts to relate corruption with the Catholic Church's role as the moral and social critics that compel believers to participate in confronting corruption and bribery. The interdisciplinarity is also the method applied in the study. It includes an exposition of the economic data of the GDP, its theological interpretation based on the story of Naboth and the king in the Old Testament, and strategic action field theory. The article begins with widespread corruption in ASEAN, then continues with a theological foundation for believers’ role as guardians of moral and social values. The Church, however, faces ritualism and religious formalism that cause faith values do not influence to eradicate corruption. Finally, by implementing the social study of Strategic Action Field (SAFs) theory, the paper proposes an anti-corruption movement as a strategic action for the Catholic Church to tackle corruption. The study found that the social study of Strategic Action Field (SAFs) theory allows the Church to develop the anti-corruption movement as the strategic action to create pastoral works to tackle corruption